2021
DOI: 10.1051/e3sconf/202126403001
|View full text |Cite
|
Sign up to set email alerts
|

Deep deformations of the upper stream of a low-pressure reservoir

Abstract: The article presents the results of the analysis of the deep deformations of the Amu Darya riverbed in the upper reaches of the low-pressure reservoir. The analysis of the combined transverse profiles of the riverbed in different sections of the upper reaches of the Takhiatash reservoir showed that the coastal zones are most intensively silted up. At the same time, the core zone with the highest flow rates is very weakly declared. The height of the silting layer along the length of the upper stream increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…When installing the model, the width of the tunnel tray was maintained using templates installed in pairs along its entire length [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When installing the model, the width of the tunnel tray was maintained using templates installed in pairs along its entire length [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…However, under certain conditions, this space is either insufficient to accommodate the outlet channel or completely absent. Therefore a large amount of excavation has to be performed [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…When testing soil pumps [13][14][15][16], it was found that parts made of electrocorundum on an epoxy-phenol-formaldehyde binder, compared with parts made of wear-resistant cast iron, increased the service life of pumps by 3-8 times. But the use of wear-resistant polymeric materials for the manufacture and coating of pump parts has not been widely used in practice due to the following reasons [17,18]: 1) polymer compositions do not provide satisfactory wear resistance at high flow rates; 2) the rough surface of polymer coatings creates additional hydraulic resistance and degrades hydraulic efficiency; 3) the quality of polymer coatings is highly dependent on strict adherence to the application technology.…”
Section: Fig 2 the Dependence Of The Intensity Of Wear Of The Impelle...mentioning
confidence: 99%
“…The analysis of the considered schemes in figure 1 and figure 2 shows that from the impact of centrifugal and inertial forces in the interblade channel of the impeller of the axial and centrifugal pumps, separation and redistribution of solid particles in the flow occur. As a result, in centrifugal pumps at the tip of the blade and axial pumps in the end gap of the impeller, the local concentration of solid particles increases compared to the average, which should be considered when determining the wear rate of these elements [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%